Working with dying people: Crises and compensations - R.C. McKay (AOSIS, 1991)
In dying and death situations health providers need to be aware of their approach toward death and their work so that they can sustain both themselves and their patterns in offering competent service. Those who work constantly with dying people need to explore (i) their motives in exposing such work, (ii) the vocational goals they set themselves, (iii) how they regard their own and their patients' deaths, (iv) what defences they use to protect themselves from the emotional impact of dying and death, and (v) what means they employ in managing stress and burnout. This article discusses these core issues and makes practical suggestions for health providers in caring for themselves and dying people.